Communication Mechanism and Optimization Strategies of Short Fitness-Based Videos on TikTok During COVID-19 Epidemic Period in China - Shi, Jinlong; Li, Gang; Zhao, Yaru; Nie, Qifan; Xue, Shuyan; Lv, Yangfan; Zhang, Yijing; Yang, Jiachen; Du, Guoxu (Frontiers in Communication, 2022)
Scientific and moderate exercise is an effective remedy to boost the immune system and minimize the risk of infection in the COVID-19 epidemic period. In this context, social media platforms play an essential role in communicating scientific fitness at home. Based on the integrated analysis of communication, physical geography and health geography, this paper takes short fitness-based videos on TikTok as the research object and comprehensively uses text analysis, mathematical statistics, and spatial analysis to reveal the characteristics of communication elements, fitness preferences, and the spatiotemporal evolution of these short videos, and to explore the communication mechanism and optimization path of short videos. The results show that: (1) The communication information focusing on "fighting against the epidemic and keeping fit at home" is made into short videos by female youth. Through the communication channels mainly composed of texts, pictures, and audio, the communication subjects carry out multi-level interactive communication with the communication objects; (2) Fitness preferences are mainly composed of dances, unarmed fitness, and fitness with equipment; (3) From the perspective of time, taking February 20 as the node, the daily number of released short videos shows a trend of "increase before decrease"; From the perspective of space, the distribution is significantly unbalanced across provinces, and the direction is not apparent; (4) This paper explores the communication mechanism and targeted optimization countermeasures of short fitness-based videos on TikTok in China's COVID-19 epidemic period.